Indications, results, and clinical impact of endoscopic ultrasound (EUS)-guided sampling in gastroenterology: European Society of Gastrointestinal Endoscopy (ESGE) Clinical Guideline - Dumonceau, J.-M.; Polkowski, M.; Larghi, A.; Vilmann, P.; Giovannini, M.; Frossard, J.-L.; Heresbach, D.; Pujol, B.; Fernández-Esparrach, G.; Vazquez-Sequeiros, E.; Ginès, A. (Endoscopy, 2011)
This article is part of a combined publication that expresses the current view of the European Society of Gastrointestinal Endoscopy (ESGE) about endoscopic ultrasound (EUS)-guided sampling in gastroenterology, including EUS-guided fine needle aspiration (EUS-FNA) and EUS-guided trucut biopsy (EUS-TCB), of submucosal tumors, diffuse esophageal/gastric wall thickening, pancreatic solid masses and cystic-appearing lesions, mediastinal lesions unrelated to lung or esophageal cancer, cancer of the esophagus, stomach, and rectum, lymph nodes of unknown origin, adrenal gland masses, and focal liver lesions. False-positive cytopathological results and needle tract seeding are also discussed. The present Clinical Guideline describes the results of EUS-guided sampling in the different clinical settings, considers the role of this technique in patient management, and makes recommendations on circumstances that warrant its use. A two-page executive summary of evidence statements and recommendations is provided. A separate Technical Guideline describes the general technique of EUS-guided sampling, particular techniques to maximize the diagnostic yield depending on the nature of the target lesion, and sample processing. The target readership for the Clinical Guideline mostly includes gastroenterologists, oncologists, internists, and surgeons while the Technical Guideline should be most useful to endoscopists who perform EUS-guided sampling.